Determination of Milligram Amounts of Thiourea, Allylthiourea and Phenylthiourea Using N-Chlorosaccharin in Acetic Acid Medium - Chauhan, R.P.S.; Ahmed, Irfan; Kumar, Avnish (Asian Journal of Chemistry, 2010)
A quick and convenient method has been developed for the micro determination of thiourea and some of its derivatives, milligram amount of the sample is allowed to react with excess of N-chlorosaccharin at room temperature for 10 min. After the reaction is over, the unconsumed reagent is back titrated iodometrically.